Alterations of the dominant faecal bacterial groups in patients with Crohn's disease of the colon. (1st February 2003) - Seksik, P; Rigottier-Gois, L; Gramet, G; Sutren, M; Pochart, P; Marteau, P; Jian, R; Doré, J
Abstract : Background and aim: The colonic microflora is involved in the pathogenesis of Crohn's disease (CD) but less than 30% of the microflora can be cultured. We investigated potential differences in the faecal microflora between patients with colonic CD in remission (n=9), patients with active colonic CD (n=8), and healthy volunteers (n=16) using culture independent techniques. Methods: Quantitative dot blot hybridisation with six radiolabelled 16S ribosomal ribonucleic acid (rRNA) targeting oligonucleotide probes was used to measure the proportions of rRNA corresponding to each phylogenetic group. Temporal temperature gradient gel electrophoresis (TTGE) of 16S rDNA was used to evaluate dominant species diversity. Results: Enterobacteria were significantly increased in active and quiescent CD. Probe additivity was significantly lower in patients (65 (11)% and 69 (6)% in active CD and quiescent CD) than in healthy controls (99 (7)%). TTGE profiles varied markedly between active and quiescent CD but were stable in healthy conditions. Conclusion: The biodiversity of the microflora remains high in patients with CD. Enterobacteria were observed significantly more frequently in CD than in health, and more than 30% of the dominant flora belonged to yet undefined phylogenetic groups.